APLIKASI PENJUALAN PRODUK KECANTIKAN PADA PT. SINERGI GLOBAL SERVIS BERBASIS ANDROID - Jett Enrico Chandra; Zyad Rusdi; Manatap Dolok Lauro (Fakultas Teknologi Informasi Universitas Tarumanagara, 2022)
Due to the pandemic, government were releasing a new rule about the restrictions that people could not go to public places like restaurants, shops, etc. It causes the sales on the PT. Sinergi Global Servis (SGS) since the beginning of the pandemic getting worse.Therefore I would love to help SGS and people that are loyal to the Martha Tilaar Group’s products to build an mobile-based application since they cannot visit and buy the product at the nearest store.For the development I used SDLC (System Development Life Cycle) method, with Waterfall model, I also used Flutter as the Framework for the programming, Dart Programming Language, MySQL for the Database, and lastly PHP for the API (Application Programming Interface) that used for sending data from database to application.The application’s feature that I build were customers can search the catalogue’s product, make an order, review a product, etc. Then the orders that was made by a customer, it went to the sales’s account and they could proceed the orders, the company also have an account and they could see transaction,absence, and stock reports.